Sistem Informasi Pemesanan Dan Penjualan Produk RK Kosmetik Pada toko Sabna Salakan Berbasis Web Mobile - Iskandar Surdin; Sutriana Sutriana (Jurnal Ilmiah Sistem Manajemen Informatika dan Komputerisasi Akuntansi, 2022)
The objectives of this research are as follows: to be able to design and build an information system for ordering and selling cosmetic brand products at the Sabna Web Mobile-based store, to provide easy information for buyers of cosmetic products to see the product they want with this information system so that it can assist in processing orders and sales of Sabna store products. Based on the research results obtained, by creating an Information System for Ordering and Sales of RK Cosmetic Products at the Mobile Web-Based Sabna Salakan Store, the system at the store can be easier and more efficient from sales, transactions, and making sales reports that are faster, accurate and structured with good.